Calibration of the BMP280 and ESP-12S Based Wireless Atmospheric Pressure Measure Equipment Using a Pressure Chamber - Laksono, Arief; Widagda, I Gusti Agung (BULETIN FISIKA; Vol 23 No 1 (2022): BULETIN FISIKA February Edition, 2021)
In order to study and practice the method of meteorological atmospheric pressure gauge calibration, the design, assembly and calibration of an experimental wireless atmospheric pressure gauge based on the BMP280 digital pressure sensor and the System on Chip ESP-12S has been carried out. Using the Vaisalla PTB330 digital barometer secondary pressure standard, the instrument is calibrated in the pressure chamber in the pressure range 850-1050 hPa with a maximum tolerance limit of ± 0.15 hPa at a 95% confidence level. Based on the test results of the correction parameters and U 95 , it shows that the reliability of the sensor interface system and the internal correction application method used in the calibration process provide calibration results that meet the requirements of the WMO standard. The precision test on repeatability conditions based on ISO5725: 1994 is also used as a measure of tool precision. Through this calibration report, the performance and accuracy of the BMP280 sensor in relation to measurements on meteorological objects, especially atmospheric pressure can be known and studied further.